Here's the question you clicked on:
Mello
If (a/b)=(c/d), prove (a+b)/(a-b)=(c+d)/(c-d).
hint : 1.Add 1 on both sides---->(1) 2.subtract 1 from both sides ---->(2) 3. divide : (1)/(2)
@Mello did u get it or should i show detailed steps??
Yes, please. My brain isn't getting it.
Im a bit lost from there.
so u must have got : \(\frac{a+b}{b}=\frac{c+d}{d}\)------->(1) right? Step 2: subtract 1 from both sides: \(\frac{a}{b}-1=\frac{c}{d}-1\) \(\frac{a-b}{b}=\frac{c-d}{d}\)------->(2) got step 2 ??
@hartnn Right. Oh subtract from the original. OK.
sorry i didn't mention that, now divide: (1) / (2) did u see how u get your final result after dividing??
How would you divide an equation by an equation?
ofcourse we can: if x=y and w=z after dividing we get (x/w)=(y/z) try dividing here. if u don't get, i'll show that step.
Oh, right. I remember learning something like that. I think I should be able to manage from here
good,let me know if u still have doubts or could not get final answer.
Alrighty, Thank you so much for the help!